Variations in HDL-carried miR-223 and miR-135a concentrations after consumption of dietary trans fat are associated with changes in blood lipid and inflammatory markers in healthy men - an exploratory study. Issue 6 (2nd June 2016) - Desgagné, Véronique; Guay, Simon-Pierre; Guérin, Renée; Corbin, François; Couture, Patrick; Lamarche, Benoit; Bouchard, Luigi
ABSTRACT: A high consumption of trans fatty acids (TFAs) is associated with an increased risk of cardiovascular diseases (CVDs). High-density lipoproteins (HDLs) have many cardioprotective properties and transport functional microRNAs (miRNAs) to recipient cells. We hypothesized that dietary TFAs modify the HDL-carried miRNA profile, therefore modulating its cardioprotective properties. We assessed whether consumption of dietary TFAs modifies HDL-carried miR-223-3p and miR-135a-3p concentration and the inter-relationship between diet-induced changes in HDL-carried miRNA concentration and CVD risk markers. In a double blind, randomized, crossover, controlled study, 9 men were fed each of 3 experimental isoenergetic diets: 1) High in industrial TFA (iTFA; 3.7% energy); 2) High in TFA from ruminants (rTFA; 3.7% energy); 3) Low in TFA (control; 0.8% energy) for 4 weeks each. HDLs were isolated by ultracentrifugation and miRNAs were quantified by RT-qPCR. Variations in HDL-miR-223-3p concentration were negatively correlated with variations in HDL-cholesterol after the iTFA diet (rs = 0.82; P = 0.007), and positively correlated with variations in C-reactive protein concentration after the rTFA diet (rs = 0.75; P = 0.020). Variations in HDL-miR-135a-3p concentration were positively correlated with variations in total triglyceride (TG) concentration following the iTFA diet (rs = −0.82; P = 0.007), and with variations in low-density lipoprotein (LDL)-TG concentration following the rTFA diet (rs = 0.83; P = 0.005), compared to the control diet. However, the consumption of dietary TFAs has no significant unidirectional impact on HDL-carried miR-223-3p and miR-135a-3p concentrations. Our results suggest that the variability in the HDL-carried miRNAs response to TFA intake, by being associated with variations in CVD risk factors, might reflect physiological changes in HDL functions.